Rheological, Functional And Antioxidant Properties Of Films Forming Solution And Active Gelatin Fillms Incorporated With Centella Asiatica (L.) Urban Extract - M.I.N. Isa; N.A.M. Rasid; N.N.M. Nazmi; N.M. Sarbon (Elsevier, 2024)
This study focused on the rheological, functional and antioxidant properties of gelatin film with C.asiatica (L.) Urban extracts added. Six film forming solutions of gelatin/glycerol/extract blended film were prepared: A (100/30/0); B (100/30/5); C (100/30/10); D (100/30/15); E (100/30/20); and F (100/30/25). Rheological, antioxidant, mechanical (tensile strength (TS) and elongation at break (EAB)), physical (water vapour permeability (WVP), FTIR analysis, scanning electron micrography) and thermal properties were characterized. The viscoelastic properties of film forming solution (FFS) incorporated with extract resulted in a well–structured system. Blended films with 25% Centella asiatica extract showed higher antioxidant activity, EAB values, glass transition and melting point but lower values for WVP and TS. These results indicate that C.asiatica (L.) Urban extracts have good potential to be incorporated into gelatin film as active film packaging. This is because it increases the mechanical properties while decreased WVP which important properties for film packaging. Furthermore the antioxidant properties of C.asiatica (L.) Urban extracts will enhance the quality of packaged food by demonstrate the immense potential of these films as food packaging materials to efficiently control bacteria growth in complex food systems